(untitled) (Bangladesh Journal of Agricultural Research, 2015)
Ten sweet potato lines/varieties were studied for growth response under NaCl salt stress condition. The rooting ability, in terms of root number, root length and root volume was studied. Growth in terms of root and shoot dry weight was also studied. A variation was recorded among the eight varieties and two lines in different doses of NaCl for growth responses in terms of rooting ability. The genotypes BARI SP-9, showed rooting ability up to 20 dS-m among the 10 genotypes. The genotypes BARI SP-2, BARI SP-3, BARI SP-7, BARI SP-9 and line SP-613 showed increase in root number upto 6 dS-m as compared to control. Accumulation of Na+ increased with a concomitant decrease in K+. Sweet potato plantlet transport less amount of Na+ and more amount of K+ to the shoot. Genotypes BARI SP-7 and BARI SP-9 showed better performance upto15dS-m. Bangladesh J. Agril. Res. 40(2): 249-257 June 2015